Estudio controlado de algunas escals del M.M.P.I. y redimiento en conducta en un grupo de adolescentes - Beyer, Alfred (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The Spanish version of the Minnesota Multiphasic Personality Inventory, edited by The University’ of Puerto Rico, was given to 85 adolescents of 17 years of age at the Naval Academy in Peru, to show the relationship between department and findings of high scores in the nine original scales. General results showed that there is a relationship (a significant one according to statistical terms) between adolescents with poor conduct and scores higher than 70 in one or several of the clinical scales. A statistical correlation on the quality of scales was not possible due to the small N of the sample.